Unlisted investments by pension funds in Namibia: an evaluation of social impact - Endjila, Ester Tegelelomuwa (Graduate School of Business (GSB), 2023)
Empirical evidence indicates that private equity in Africa is important for proliferating social and economic development in the form of job creation, poverty reduction, economic empowerment and reducing dependency on foreign aid. Namibia presents a unique case in that ‘unlisted investments', as they are known in the country, are both required and regulated for pension funds, creating an opportunity to evaluate the impact thereof. This study uses objective company data to examine the effect of pension fund unlisted investment capital on social outcomes in Namibia, by reviewing this data qualitatively in the first instance and then quantitatively. The qualitative findings indicate that 92% of the Special Purpose Vehicles (SPVs) examined have impact objectives in their investment plans and therefore aim to have some kind of impact as a starting point. However, it is found that frameworks for measuring the desired impacts are not well demonstrated. The quantitative regression analysis does not provide enough evidence to prove a significant and positive relationship between incremental unlisted investment capital contributed and variation in total employment (used to represent social impact). The study identifies the lack of impact data in the industry as a concern and recommends the incorporation of an impact measurement framework as part of the regulatory framework for unlisted investments, in order to appropriately meet the objectives for which the unlisted investment requirement was created